Collectively stabilizing and orienting posterior migratory forces disperses cell clusters in vivo - B. Lin (Nature Portfolio, 2020)
During development, primordial germ cell clusters undergo dispersal but how cell–cell adhesion and contractility are coordinated during this process in vivo is unclear. Here, the authors show that Drosophila primordial germ cells utilize migratory forces to disperse through G-protein coupled receptor mediated collective guidance of front-back polarity outwards from the cluster.